Geneology of Religious Thought and Activities of Ex-Terrorist Prisoners in Surakarta - Abdul Matin bin Salman; Nur Rohman; Fuad Muhammad Zein (DINIKA : Academic Journal of Islamic Studies, 2023)
This article aims to shed light on the roots of ex-jihadists' thinking and activities following their exit from the de-radicalisation programme. It seeks to continue the discussion on radicalism and de-radicalisation in Indonesia. Based on field data and interviews with several informants in Surakarta, this article explains that former jihadists have different ideological genealogies. However, after their departure from these groups and activities, there are similarities in terms of survival strategies. The results of this study also show that almost all of them experienced obstacles when they first returned to normal society. But now they have managed to carry out their activities as traders and entrepreneurs in their own way. Some of them are even able to create associations that voice the importance of upholding the spirit of nationalism and rejecting acts of terror. Applying Weber's theory of individual action, this article also shows a shift in rational action choices that are intertwined with quite complex interests.